Intravoxel Incoherent Motion Diffusion-Weighted Imaging Versus Dynamic Contrast-Enhanced Magnetic Resonance Imaging: Comparison of the Diagnostic Performance of Perfusion-Related Parameters in Breast. Issue 1 (January 2018) - Jiang, Lei; Lu, Xu; Hua, Bin; Gao, Jiayin; Zheng, Dandan; Zhou, Yiming
Abstract : Objective: The aim of this study was to investigate the diagnostic performance of the perfusion-related parameters of intravoxel incoherent motion (IVIM) imaging for breast lesions, compared with dynamic contrast-enhanced magnetic resonance imaging (DCE MRI). Methods: Fifty-nine patients with both IVIM imaging and subsequent DCE MRI were enrolled. Perfusion-related parameters of IVIM imaging (perfusion fraction, f ; pseudo–diffusion coefficient, D *), as well as model-based and model-free parameters of DCE MRI, were measured. Receiver operating characteristic curve analysis and correlations between the IVIM and DCE MRI parameters were performed. Results: Thirty-one malignant and 35 benign lesions were pathologically proved. The area under the receiver operating characteristic curves (AUC) of D * plus f (AUC f + D * ) was 0.834. The combined AUC of all model-based DCE MRI parameters (AUCmodel-based ) was 0.904. The combined AUC of all model-free DCE MRI parameters (AUCmodel-free) was 0.876. AUC f + D * had no significant difference with either AUCmodel-based or AUCmodel-free . No significant correlation was found between f or D * and DCE-derived parameters. Conclusions: Intravoxel incoherent motion imaging has the same value in differentiating malignant and benign breast lesions, compared with DCE MRI, in terms of perfusion-related parameters.